Karakteristik Komposit Biotermoplastik Berbasis Pati Termoplastis/ Glukomanan Termoplastis/Poli Asam Laktat Dalam Variasi Jenis dan Konsentrasi Filler - Siringo-Ringo , Putri Agnesia; Harsojuwono, Bambang Admadi; Suwariani, Ni Putu; Hartiati, Amna; Hartiati, Sri (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Biothermoplastic composites are eco-friendly materials that degrade more quickly. These composites are a mixture of biologically-based polymers that melt when heated and solidify when cooled, making them a potential solution for sustainable packaging materials. This study aims to determine the effect of various types and concentrations of fillers on the characteristics of biothermoplastic composites, as well as to identify the combination of filler type and concentration that produces the best characteristics in thermoplastic starch/thermoplastic glucomannan/polylactic acid (TPS/TPG/PLA) composites. The research used a Completely Randomized Design (CRD) factorial with the first factor being the type of filler (J), namely ZnO, Clay, and CaCO₃, while the second factor was the filler concentration (K), which was 5%, 7.5%, and 10% of the matrix material. Therefore, there were 9 treatment combinations, each repeated twice. The variables observed in this study were tensile strength, elongation at break, elasticity (Young's modulus), swelling, density, melting point, and biodegradation time. The data obtained were analyzed using variance analysis and followed by the Honest Significant Difference (HSD) test. The results showed that the type and concentration of filler had a significant influence on tensile strength, elongation at break, elasticity, swelling, density, melting point, and biodegradation time. The best biothermoplastic composite was obtained using 10% clay filler, with a tensile strength of 41.88 MPa, elongation at break of 0.68%, elasticity of 6.16 GPa, swelling of 0.48%, density of 1.01 g/cm³, a melting point of 170.05°C, and a biodegradation time of 24.5 days. The characteristics of the TPS/TPG/PLA biothermoplastic composite mostly meet SNI and international standards, except for elongation at break.